Eculizumab use in neuromyelitis optica spectrum disorders: routine clinical care data from a european cohort - Ringelstein, Marius; Emmer, Alexander; Jarius, Sven; Korporal-Kuhnke, Mirjam; Wildemann, Brigitte (Neurology, 2024)
Background and Objectives - Attack prevention is crucial in managing neuromyelitis optica spectrum disorders (NMOSDs). Eculizumab (ECU), an inhibitor of the terminal complement cascade, was highly effective in preventing attacks in a phase III trial of aquaporin-4 (AQP4)-IgG seropositive(+) NMOSDs. In this article, we evaluated effectiveness and safety of ECU in routine clinical care. - Methods - We retrospectively evaluated patients with AQP4-IgG+ NMOSD treated with ECU between December 2014 and April 2022 at 20 German and 1 Austrian university center(s) of the Neuromyelitis Optica Study Group (NEMOS) by chart review. Primary outcomes were effectiveness (assessed using annualized attack rate [AAR], MRI activity, and disability changes [Expanded Disability Status Scale EDSS]) and safety (including adverse events, mortality, and attacks after meningococcal vaccinations), analyzed by descriptive statistics. - Results - Fifty-two patients (87% female, age 55.0 ± 16.3 years) received ECU for 16.2 (interquartile range [IQR] 9.6 - 21.7) months. Forty-five patients (87%) received meningococcal vaccination before starting ECU, 9 with concomitant oral prednisone and 36 without. Seven of the latter (19%) experienced attacks shortly after vaccination (median: 9 days, IQR 6-10 days). No postvaccinal attack occurred in the 9 patients vaccinated while on oral prednisone before starting ECU and in 25 (re-)vaccinated while on ECU. During ECU therapy, 88% of patients were attack-free. The median AAR decreased from 1.0 (range 0-4) in the 2 years preceding ECU to 0 (range 0-0.8; p < 0.001). The EDSS score from start to the last follow-up was stable (median 6.0), and the proportion of patients with new T2-enhancing or gadolinium-enhancing MRI lesions in the brain and spinal cord decreased. Seven patients (13%) experienced serious infections. Five patients (10%; median age 53.7 years) died on ECU treatment (1 from myocardial infarction, 1 from ileus with secondary sepsis, and 3 from systemic infection, including 1 meningococcal sepsis), 4 were older than 60 years and severely disabled at ECU treatment start (EDSS score ≥ 7). The overall discontinuation rate was 19%. - Discussion - Eculizumab proved to be effective in preventing NMOSD attacks. An increased risk of attacks after meningococcal vaccination before ECU start and potentially fatal systemic infections during ECU - particularly in patients with comorbidities - must be considered. Further research is necessary to explore optimal timing for meningococcal vaccinations. - Classification of Evidence - This study provides Class IV evidence that eculizumab reduces annualized attack rates and new MRI lesions in AQP4-IgG+ patients with NMOSD.
Gesehen am 24.06.2025